SINERGI KOMPETENSI, KOMITMEN, DAN KOMUNIKASI ORGANISASI DALAM MENDORONG KINERJA KARYAWAN PT. BPR SILIWANGI TASIKMALAYA - Erwansyah, Sanni (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to examine the influence of competence, organizational commitment, and organizational communication on employee performance at PT. BPR Siliwangi Tasikmalaya. A quantitative approach was applied using a survey method, with the entire population of 40 employees taken as the sample. The independent variables consist of competence, organizational commitment, and organizational communication, while the dependent variable is employee performance. Validity and reliability tests were conducted using product moment correlation and Cronbach’s Alpha. The data were analyzed using multiple linear regression. The results show that all three independent variables have a positive and significant effect on employee performance, both partially and simultaneously. The model explains 57.7% of the variance in employee performance. These findings indicate that improving employee skills and knowledge, strengthening their loyalty and attachment to the organization, and fostering effective communication in the workplace are key strategies for enhancing overall employee performance.